Neurological Deterioration After Hemivertebrectomy for Congenital Thoracic Kyphoscoliosis with Myelopathy: A Case Report. Issue 3 (July 2021) - Matsumoto, Yuki; Watanabe, Kota; Suzuki, Satoshi; Nori, Satoshi; Tsuji, Osahiko; Nagoshi, Narihito; Okada, Eijiro; Yagi, Mitsuru; Fujita, Nobuyuki; Nakamura, Masaya; Matsumoto, Morio
Abstract : Case: A 14-year-old adolescent boy with congenital kyphoscoliosis with T5 hemivertebra visited our hospital complaining gait disturbance. The T5 hemivertebra was resected posteriorly, and kyphosis at T4 to T7 was corrected from 43° to 36°. However, neurological status gradually deteriorated after surgery. Surgery to reduce kyphosis by bending the rods was performed with intraoperative ultrasonography, which resulted in spinal cord decompression and repulsation of the spinal cord. The muscle strength of the lower extremities improved immediately after surgery. Conclusion: Correction surgery for congenital kyphoscoliosis has high risk of perioperative neurological deterioration. Ultrasonography may be a useful tool for monitoring status of the spinal cord.